Estimativa da variação do estoque de carbono do solo em diferentes cenários de uso e manejo agropecuário no estado do Maranhão - Mendes, Telmo José [UNESP] (2015)
Soils feature significant variations in soil carbon stocks through in landuse changes, management practices and intrinsic characteristics. The objective of this study was to estimate the changes in soil carbon stock under different scenarios of land use and agricultural management in the Maranhão State, considering the conversion of conventional agriculture to conservationist management systems. The estimate for soil carbon storage (0-30cm) was approximately 24.74 Mt C. Changes in soil carbon stocks were estimated from a scenario (S0) to the current scenario (2010), followed by the adoption of conservationist scenario by the year 2030. The pasturelands are under soils with the highest carbon stocks (62.19 Mg ha-1), the forestry lands with 61.60 Mg ha-1 and agricultural lands with 38.28 Mg ha-1. The conversion of native vegetation for intensive agricultural use contributed to soil carbon losses of 1.57 Mt C, with grazing areas accounting for 1.36 Mt C and agricultural lands for 0.21 Mt C by 2010. The replacement of intensive farming systems by conservationist agricultural practices in the current areas has a technical potential for soil carbon sequestration of 0.6 Mt by 2030, with livestock and agricultural lands accounting for 0.54 Mt C and 0.03 Mt C, respectively